Penerapan Digital Marketing dan Inovasi Model pada Produsen Sepatu Kulit (Bapak Misbah di RT. 06. RW. 01 Desa Buduran Sidoarjo) - Darno Darno; Wulan SE Purnamasari; Nurul Laili Fitriya; Eko Purwanto; Jaya Adi Gama; Kuswana Rama Rama Destian; Camelia Dewi Rahmawati; Andre Brata K; Wahyu Putra Budi (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
Shoes serve to protect our feet from dust and dirt, shoes are one of the important aspects to perfect one's appearance. Armed with experience in making shoes, Mr. Misbah, a resident of Banjarsari village, Buduran District, Sidoarjo Regency, Mr. Misbah started a business selling shoes with a conventional sales and marketing system. Until the covid 19 pandemic, which had to divert office activities to work from home (WFH) and the online learning process, resulted in a decrease in the number of shoe orders. Mr. Misbah couldn't help but have to close his shop temporarily because none of the orders came in. In the new normal era after this pandemic. Therefore, the Community Service (PKM) team helps our partner, Mr. Misbah, especially in finding alternatives to online marketing, including models and how to take photos of their products.